Implementasi Etika Bisnis Islam dalam Operasional Koperasi Pegawai Mahkamah Syar’iyah di Provinsi Aceh - Hanifa; Muhammad Adnan; Khairul Amri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
Business ethics holds a significant position in the economy, particularly within societies that prioritize religious values. In Islamic teachings, business ethics are rooted in religious principles and strong moral foundations. This study examines the application of Islamic business ethics in the Employee Cooperative of the Sharia Court in Aceh using a descriptive qualitative methodology. Data collection methods included interviews, observations, and documentation, which were subsequently analyzed through data reduction, presentation, and verification techniques. The findings reveal that the cooperative adheres to fundamental Islamic business ethics principles, such as unity, balance, free will, responsibility, and truthfulness. The management of remaining business results (SHU) is conducted equitably and proportionally, allowing members to participate voluntarily without compulsion. Furthermore, the cooperative fosters harmonious interactions among members by upholding honesty, transparency, and openness. These practices cultivate a just and ethical cooperative environment aligned with Islamic values, reinforcing integrity and fairness in its operations.